2017
DOI: 10.1002/nau.23362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vesical and perfusion pressure on perfusate flow, and flow on vesical pressure, in the isolated perfused working pig bladder reveal a potential mechanism for the regulation of detrusor compliance

Abstract: Perfusate flow is dependent on bladder perfusion pressure, and not necessarily reciprocally dependent on vesical pressure. Vesical pressure is highly sensitive to the level of perfusate flow, which supports the hypothesis that vesical pressure is dependent on the level of detrusor smooth muscle contractile activity (tone), and that compliance is dependent on bladder perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…Although porcine models have been developed to evaluate whole bladder function ex vivo, few have expressly focused on evaluation of bladder perfusion. In a previous study, we prepared an isolated perfused working pig bladder model which confirmed that decreased bladder perfusion occurs with increasing vesical pressure during the filling phase . This study demonstrated that normal bladder filling may be associated with transient periods of relative ischemia.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although porcine models have been developed to evaluate whole bladder function ex vivo, few have expressly focused on evaluation of bladder perfusion. In a previous study, we prepared an isolated perfused working pig bladder model which confirmed that decreased bladder perfusion occurs with increasing vesical pressure during the filling phase . This study demonstrated that normal bladder filling may be associated with transient periods of relative ischemia.…”
Section: Introductionmentioning
confidence: 53%
“…At the time of use, additional dissection was performed to remove excess tissue, and each bladder was weighed. Cannulation of the right and left vesical arteries as well as one ureter (used for intravesical pressure monitoring) was performed and a urethral catheter was placed as previously described . A 22‐gauge Jelco IV catheter (Smiths Medical, Minneapolis, MN) was carefully inserted into the anterior detrusor muscle with care taken not to violate the bladder lumen.…”
Section: Methodsmentioning
confidence: 99%
“…Bladders from adult male (castrated) and female pigs were obtained from local abattoirs immediately after slaughter. As previously described, the dissection included removal of the bladder, urethra, ureters, and vascular tree including a section of the aorta, iliac arteries, branching vesical arteries, and corresponding venous system . The aorta was cannulated and cold‐perfused with heparinized Krebs‐Henseleit (KH) buffer .…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, the dissection included removal of the bladder, urethra, ureters, and vascular tree including a section of the aorta, iliac arteries, branching vesical arteries, and corresponding venous system . The aorta was cannulated and cold‐perfused with heparinized Krebs‐Henseleit (KH) buffer . Tissues were stored in 3‐(N‐morpholino) propanesulfonic acid (MOPS) based buffer and transported to the lab for use within approximately 3 hours or stored for use within 48 hours .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation